Comparison of outcomes of monochorionic twin pregnancies conceived by assisted reproductive technology vs. spontaneous conceptions: A systematic review and meta-analysis - Wang, Minmin; Chai, Jingjing (Frontiers in Pediatrics, 2022)
Background This review aimed to assess if monochorionic twin pregnancies conceived by assisted conception have worse maternal and neonatal outcomes as compared to those conceived naturally. Methods Datasets of PubMed, ScienceDirect, CENTRAL, Embase, and Google Scholar were searched for studies comparing maternal and neonatal outcomes of monochorionic twin pregnancies conceived by assisted vs. spontaneous methods. Results Eight studies comparing 337 assisted with 2,711 spontaneously conceived monochorionic twin pregnancies were included. Meta-analysis revealed that the mode of conception of monochorionic twin pregnancies had no impact on the risk of hypertensive disorders of pregnancy (HDP) (OR: 1.36 95% CI, 0.73, 2.54 I2 = 9% p = 0.03), twin-twin transfusion syndrome (TTTS) (OR: 0.83 95% CI, 0.52, 1.31 I2 = 0% p = 0.42), and very preterm delivery (OR: 1.18 95% CI, 0.74, 1.88 I2 = 41% p = 0.49). We noted no statistically significant difference in the mean birth weights (MD: −17.66 95% CI, −157.23, 121.91 I2 = 82% p = 0.80), risk of intra-uterine death (OR: 0.90 95% CI, 0.51, 1.60 I2 = 36% p = 0.73) and small for gestational age between the two groups (OR: 0.92 95% CI, 0.67, 1.26 I2 = 0% p = 0.59). There was an increased risk of caesarean sections (OR: 1.34 95% CI, 1.00, 1.80 I2 = 0% p = 0.05) and neonatal death with assisted conceptions as compared to spontaneous conceptions (OR: 2.35 95% CI, 1.11, 5.01 I2 = 37% p = 0.03). Conclusion Monochorionic twin pregnancies conceived via assisted reproductive technology have a heightened risk of cesarean section and neonatal deaths. However, there is a need for further studies to supplement current evidence. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=325133, identifier: CRD42022325133.